"Be Silent in that Solitude": Women and the Subversion of Silence in Surah "Al-Mujadilah" and Poe's "Ligeia". Issue 2 (3rd July 2019) - Hamdan, Mohammed
ABSTRACT: This essay probes the notion of silence and women's acoustic subversion in Surah "Al-Mujādilah" in the Holy Qurʾān and Edgar Allan Poe's "Ligeia." In the Islamic tradition and Poe's literary texts, women's voices and subjectivity are limited due to their conventional, hermeneutical association with the presumed hidden fear of corruption and violation in androcentric societies. The essay not only points to the Qurʾānic influence on Poe's treatment of women as silent and submissive, but also seeks to position Poe's female characters in relation to the Qurʾānic model of subversive femininity. Within both narratives, women are traditionally designated to play specific role models that seem to idealize them as passive linguistic constructs in their communities. The essay, however, reconsiders the orthodox patriarchal representation of women in the Qurʾānic chapter and Poe's text and rather suggests a rereading of their silence as a subversive speech-act whereby they question and reevaluate the ontological tendency to view them as acoustic objects to male authority.